Contrast-enhanced cardiovascular magnetic resonance imaging of coronary vessel wall: state of art. (February 2014) - Kuo, Yen-Shu; Kelle, Sebastian; Lee, Charlotte; Hinojar, Rocio; Nagel, Eike; Botnar, Rene; Puntmann, Valentina O
<x xml:space="preserve">Abstract</x> Coronary wall imaging by cardiovascular magnetic resonance (CMR) emerges as a promising method to detect vascular injury and remodeling directly within the coronary vascular wall. In this review, the current evidence on coronary wall enhancement using CMR is presented and summarized, with particular focus on its ability to detect inflammation in atherosclerosis, Takayasu's arteritis, acute coronary syndromes and immune-mediated inflammatory vasculitides. The authors review the possible mechanisms of coronary wall contrast enhancement on CMR and discuss the technical considerations and limitations. Lastly, the potential clinical applications and possibilities for future research are proposed.